Post-Golgi anterograde transport requires GARP-dependent endosome-to-TGN retrograde transport - Hirata, Tetsuya; Fujita, Morihisa; Nakamura, Shota; Gotoh, Kazuyoshi; Motooka, Daisuke; Murakami, Yoshiko; Maeda, Yusuke; Kinoshita, Taroh (Molecular biology of the cell, 2015)
The importance of endosome-to– trans-Golgi network (TGN) retrograde transport in the anterograde transport of proteins is unclear. In this study, genome-wide screening of the factors necessary for efficient anterograde protein transport in human haploid cells identified subunits of the Golgi-associated retrograde protein (GARP) complex, a tethering factor involved in endosome-to-TGN transport. Knockout (KO) of each of the four GARP subunits, VPS51–VPS54, in HEK293 cells caused severely defective anterograde transport of both glycosylphosphatidylinositol (GPI)-anchored and transmembrane proteins from the TGN. Overexpression of VAMP4, v-SNARE, in VPS54-KO cells partially restored not only endosome-to-TGN retrograde transport, but also anterograde transport of both GPI-anchored and transmembrane proteins. Further screening for genes whose overexpression normalized the VPS54-KO phenotype identified TMEM87A, encoding an uncharacterized Golgi-resident membrane protein. Overexpression of TMEM87A or its close homologue TMEM87B in VPS54-KO cells partially restored endosome-to-TGN retrograde transport and anterograde transport. Therefore GARP- and VAMP4-dependent endosome-to-TGN retrograde transport is required for recycling of molecules critical for efficient post-Golgi anterograde transport of cell-surface integral membrane proteins. In addition, TMEM87A and TMEM87B are involved in endosome-to-TGN retrograde transport.